Assessing Water Absorption and Root-Shoot Dynamics of Native Philippine Tree Species for Flood Mitigation and Environmental Management - Goyo, Shiella Lynn Dali-on; Corbita, Victor Lobrigas; Acog, Glendel Cotejo; Balaba, Diana Rose; Estrada, Jessa Joy Tomoc; Mercado, Joel Andig (Jurnal Sylva Lestari, 2025)
Over the years, excessive stormwater run-off has been a primary environmental concern in almost every part of the world. This study aimed to assess the water absorption capacity and root-shoot ratio of the three native species, namely Vitex parviflora, Pterocarpus indicus, and Diospyrus discolor, in the Philippines. The study used an experimental design with a total number of 63 experimental seedlings. After over a month of transplanting, the researchers collected the data by uprooting 1 sample per box and recording its weight. The uprooted samples were then submerged into a container with enough water, and the plant waited until it absorbed enough water before being weighed again. Root and shoot ratio were also computed using its dry weight. The results showed a significant difference in terms of absorption rate between the three native species. V. parviflora garnered the highest water absorption rate, followed by P. indicus and D. discolor. Root-shoot ratio was highest in D. discolor while lowest in V. parviflora. No significant correlation was found between root and shoot biomass regarding water absorption capacity. These findings highlight the importance of selecting specific tree species for environmental management and flood mitigation efforts in the Philippines. Keywords: biomass, native species, stormwater run-off, water absorption